PENGARUH pH DAN KONSENTRASI STARTER Saccharomyces cerevisiae TERHADAP RENDEMEN MINYAK KELAPA HASIL FERMENTASI SEBAGAI PERANGKAT PEMBELAJARAN BIOTEKNOLOGI SEDERHANA - Firdaus, Firdaus (JSTT, 2015)
This study aimed to describe the influence of pH and concentration starter Saccharomyces cerevisiae to the yield of coconut-oil fermentation as a result biotechnology simple learning device. This study using a randomized complete block design with a factorial design by treatment three times replications. The research variables are the effect of pH and the concentration of starter Saccharomyces cerevisiae. The results showed that the treatment of pH 4 and addition of starter Saccharomyces cerevisiae as much as 10% produce the highest yield of coconut oil, whereas the treatment which produces palm oil yield is the lowest pH 7 and concentration starter 0%. The results of palm oil yield obtained ranges from 15.00% to 33.67%.Â The results of the study would be continued by the manufacture of teaching biology particularly biotechnology materials in the form of teaching materials, teacher guides and student guides. The procedure used is a modification model manufacture Thiagarajan or 4-D models. The resulting learning device, then assessed by an expert content, design experts, media experts, partners teachers and students high school Al-Azhar Palu. The percentage value of teaching materials is 88% (good category), teachers' guidebook 88% (good category) and students guidebooks 91% (excellent category). Therefore the learning devices generated in this study proper to use.